Can Plant-Based Natural Flax Replace Basalt and E-Glass for Fiber-Reinforced Polymer Tubular Energy Absorbers? A Comparative Study on Quasi-Static Axial Crushing - Yan, Libo; Wang, Bo; Kasal, Bohumil (Frontiers in Materials, 2017)
Using plant-based natural fibres to substitute glass fibres as reinforcement of composite materials is of particular interest due to their economic, technical and environmental significance. One potential application of plant-based natural fibre reinforced polymer (FRP) composites is in automotive engineering as crushable energy absorbers. Current study experimentally investigated and compared the energy absorption efficiency of plant-based natural flax, mineral-based basalt and glass FRP composite tubular energy absorbers subjected to quasi-static axial crushing. The effects of number of flax fabric layer, the use of foam-filler and the type of fibre materials on the crashworthiness characteristics and energy absorption capacities were discussed. In addition, the failure mechanisms of the hollow and foam-filled flax, basalt and glass FRP tubes in quasi-static axial crushing were analysed and compared. The test results showed that the energy absorption capabilities of both hollow and foam-filled energy absorbers made of flax were superior to the corresponding energy absorbers made of basalt and were close to energy absorbers made of glass. This study therefore indicated that flax fibre has the great potential to be suitable replacement of basalt and glass fibres for crushable energy absorber application.